2014
DOI: 10.1097/sla.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Trial of Bariatric Surgery Versus Intensive Medical Weight Management on Diabetes Remission in Type 2 Diabetic Patients Who Do NOT Meet NIH Criteria for Surgery and the Role of Soluble RAGE as a Novel Biomarker of Success

Abstract: Structured Abstract Objective To compare bariatric surgery vs. intensive medical weight management (MWM) in patients with type 2 diabetes (T2DM) who do not meet current NIH criteria for bariatric surgery. To assess whether the soluble form of receptor for advanced glycation endproducts (sRAGE) is a biomarker to identify patients most likely to benefit from surgery. Summary Background Data There are few studies comparing surgery to MWM for patients with T2DM and BMI < 35. Methods 57 patients with T2DM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 25 publications
7
66
1
1
Order By: Relevance
“…2A). Numerous RCTs with postoperative follow-up ranging between 1 and 5 years have consistently documented sustained diabetes remission in 30-63% of patients (LoE IB) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Available data suggest an erosion of diabetes remission over time: 35-50% or more of patients who initially achieve remission of diabetes eventually experience recurrence.…”
Section: Summary Of Evidence: Clinical and Biological Rationale For Smentioning
confidence: 99%
See 3 more Smart Citations
“…2A). Numerous RCTs with postoperative follow-up ranging between 1 and 5 years have consistently documented sustained diabetes remission in 30-63% of patients (LoE IB) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Available data suggest an erosion of diabetes remission over time: 35-50% or more of patients who initially achieve remission of diabetes eventually experience recurrence.…”
Section: Summary Of Evidence: Clinical and Biological Rationale For Smentioning
confidence: 99%
“…Beyond improving glycemia, bariatric/ metabolic surgery has been shown to confer additional health benefits in RCTs, including greater reductions compared with medical/lifestyle interventions in other CVD risk factors (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and enhancements in quality-of-life measures (LoE IB) (15,19,20). Improvements in other critical outcomes, such as micro-and macrovascular complications of diabetes, CVD, cancer, and death, have been observed only in nonrandomized studies (LoE IIA) (3,52,57,(61)(62)(63)(64)(65).…”
Section: Summary Of Evidence: Clinical and Biological Rationale For Smentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a study by Diamanti-Kandarakis, et al showed that long term consumption of AGEs was associated with higher levels of fasting glucose, insulin and serum AGEs, as well as increased AGEs localization and RAGE staining in rat ovarian tissue [34]. Interestingly, diet-induced weight loss has been shown to increase serum sRAGE levels [26,78], and higher baseline sRAGE was associated with better weight loss outcome following bariatric surgery [79].…”
Section: Ages and Their Two Receptors Rage And Sragementioning
confidence: 99%